Pengaruh Penggunaan Metode Eksperiman, Pembelajaran Konvensional Dan Motivasi Belajar Terhadap Prestasi Belajar Digital Taruna DIII TNU 9A dan TNU 9B Akademi Teknik Dan Keselamatan Penerbangan Surabaya - Moch. Rifa'i (Jurnal Penelitian)
To give clearness in this research, it is required to formula the problems review of realeted literatures are: 1) is there a learning achievement difference in Digital Technique among Experimental Methodes tudents and Conventional Learning studenst? 2). Is there a learning achievment different in Digital Technique between high and low learning motivation students? 3). Is there an interaction among Experimental Methode, Coventional Learning and learning motivation in influencing Digital Technique learning achievment class DIII TNU 9A and DIII TNU 9B ATKP Surabaya.Population is class DIII TNU 9A and DIII TNU 9B ATKP Surabaya. The class is taken with one semester experience in First Semester, so students do not find standard study pattern and then give straight assessment to certain Learning. Sample of students is one class TNU 9A 20 students use Experimental Methode and one class TNU 9B 20 cadets use Conventional Learning system each randomly. Selected and depend on teacher’s readiness to accept the process.This research uses quantitative approach in experimental frame.the group is divided in two, experimental and control group. Experimental group uses Experimental Methode, while control group use conventional learning (direct teaching ). In this research ,the compared learning method is Experimental Method, Conventional learning method,and motivation,which is grouped into two : high and low motivation, so research design is questionnaire and test, while data analysis uses two ways ANAVA and SPSS.From hypothesis I, Ha is accepted and Ho is rejekted, hypothesis says ” there is learning achivment difference in Digital Technique among Experimental Method students and Conventional Learning students. From hypothesis 2, Ha is accepted and Ho is rejected. Thus, there is learning achivement difference in Digital Technique among high motivation students and low motivation students. From hypotesis 3, Ha is accepted and Ho is rejected, hypothesis says ” there is interaction among Experimental Method, conventional learning and learning Motivation in influencing Digital Techniquel earning achievment class DIII TNU 9A and DIII TNU 9B ATKP Surabaya.